Analysis of the Impact of Development Infrastructure Development on Settlement Communities - Muhammad Aunirrouf; Ronny Durrotun Nasihien (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2019)
The impact of the development of Infrastructure development on the Community of Settlement Areas on Jalan Pasar Nambangan, Kenjeran, Surabaya needs to be evaluated on 700 meters of Roads and Channels that have been installed in the location and sought the satisfaction of the local community after the construction of the Infrastructure. By using several methods including looking for quality paving, analyzing rainfall using the Log Person III method, and Seeking Community Satisfaction as a benchmark of this researcher, where the results of each analysis with optimal results, where the Road in the form of Paving blocks using concrete quality I with the crushed voltage is 38.22 MPa which will have an impact on the life of the road and in the good category, then for the channel produce a comparison of Q Channels with Q Plan 0.104237837 m3 / sec: 0.051493258 m3 / sec, which (channel conditions are safe or able to accept Q Plan) which will later has an impact on channel capacity in the next 10 years and the last of the 75 Community Respondents shows 54.22% Very Satisfied from the existence of the Infrastructure which has a good impact to support activities in the daily lives of the community.